Extrajudicial Killing Dalam Kebijakan War on Drugs di Republic of Philippines: Melanggar Statuta Roma? - Muthmainnah, Aisyah (Faculty of Law, Universitas Jambi, 2023)
This article aims to find out and analyze whether extrajudicial killings arising from the war on drug policy in the Philippines can be the jurisdiction of the International Criminal Court (ICC). This article uses juridical-normative research with a legislative, historical and conceptual approach. The act of extrajudicial killing due to the war on drug policy in the Philippines violates the provisions in the Rome Statute. The Philippines itself was a State Party of the Rome Statute although in the end the Philippines withdrew from the Rome Statute. However, this cannot change the jurisdiction of the ICC to conduct investigations into extrajudicial killings in the Philippines. Extrajudicial killing is a violation of human rights as stipulated in the Universal Declaration of Human Rights and related conventions. The act of extrajudicial killing due to the war on drug policy becomes the jurisdiction of the ICC under Article 7 paragraph 1 of the Rome Statute of 1998, namely crimes against humanity as part of murder. In establishing a crime the ICC uses elements of crimes. Therefore, extrajudicial killings that occur in the Philippines can be the jurisdiction of the ICC.